2019
DOI: 10.3928/1081597x-20190416-01
|View full text |Cite
|
Sign up to set email alerts
|

SMILE With Low Energy Levels: Assessment of Early Visual and Optical Quality Recovery

Abstract: PURPOSE: To assess early visual and optical quality recovery according to preoperative refraction after small incision lenticule extraction (SMILE) at low energy level for myopia and myopic astigmatism treatment. METHODS: This prospective study included 101 eyes of 101 patients separated into three groups: low myopia (30 eyes), with a mean spherical equivalent (SE) of −2.13 ± 0.73 diopters (D); moderate myopia (33 eyes), with a mean SE of −4.53 ± 0.86 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Since the density of the cornea decreases progressively towards the deeper layer of the stroma [25], photodisruption becomes more irregular, giving rise to a higher straylight value in eyes with larger ablation ratio. Using double-pass aberrometry, several studies also reported that the increase in postoperative objective scatter index (OSI) was correlated with the preoperative spherical equivalent [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Since the density of the cornea decreases progressively towards the deeper layer of the stroma [25], photodisruption becomes more irregular, giving rise to a higher straylight value in eyes with larger ablation ratio. Using double-pass aberrometry, several studies also reported that the increase in postoperative objective scatter index (OSI) was correlated with the preoperative spherical equivalent [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The optical quality refers to the evaluation of the optical beam from the cornea to the retina. The global point spread function analysis are objective measurements of this optical quality [7]. In order to correct vision after cataract surgery, it is important to evaluate not only visual acuity but also optical quality.…”
Section: Introductionmentioning
confidence: 99%
“…Early approaches by Donate and Thaëron [19] introduced the concept of low energy levels to facilitate swift visual recovery following lenticule extraction. In their pioneering study, they maintained symmetric spot and track distances at 4.5µm each, while lowering pulse energy from 180nJ to 100nJ for the study group, resulting in improved early recovery.…”
Section: Discussionmentioning
confidence: 99%